COVID-19 infection in patients with malignant diseases - Gojković Zdenka; Đokanović Dejan; Nikić Gordan; Jović-Đokanović Olja; Mavija Zoran; Rakita Ivanka; Jungić Saša; Vještica Milka; Berendika Jelena; Višekruna Tamara (Vojnosanitetski Pregled)
nema